(untitled) (African Journal of Biomedical Research, 2020)
The liver is constantly exposed to harmful effects of different chemical substances it detoxifies, and it is prone to inflammation which may lead to liver disease. This study investigated the methanol leaf extract of Cuphea hyssopifolia (CH) in preventing liver damage on paracetamol-induced hepatotoxicity in experimental rats. Twenty-five wistar rats were grouped into groups 1 and 2 which served as controls (positive and negative) receiving normal saline 10 ml/kg, groups 3 and 4 were administered 200 mg/kg and 400 mg/kg of Cuphea hyssopifolia leaves extract respectively, while group 5 received silymarin 100 mg/kg (standard drug treatment). Hepatotoxicity was induced with 3 g/kg of paracetamol (PCM) on the 7th day in all the animal groups except the positive control group (Group 1). At the end of the experiment, blood samples were collected for biochemical indices (liver enzymes and antioxidants) and liver tissue for histology. CH significantly (p < 0.05) reduced the raised liver enzymes level, and also increased serum levels of superoxide dismutase and catalase, while reducing lipid peroxidation level via a decrease in serum malondialdehyde measure when compared with the PCM-treated (negative) control group. The findings revealed that the methanol leaf extract of Cuphea hyssopifolia possesses potent hepatoprotective activity.